'Modernity': the historical ontology - Ponti Venter (Acta Academica)
The article focuses on a fundamental and generally disregarded aspect of modern thought: the turn in eighteenth-century philosophy towards a historical ontology. The works of selected intellectuals such as Defoe and Rousseau (in contrast to Hobbes) highlight the shift away from a static, hierarchical ontology with God as the highest structuring force, in the direction of a historical ontology with an inherent teleology and the dominance of reason as its e.schaton - progress between the dialectically related poles of nature and culture. This historical ontology has since been taken up by important nineteenth-century thinkers such as Hegel, Comte, Marx and Darwin, and also makes its influence felt in the irrationalist tradition (albeit with the poles inverted), and even in the present day in various areas of culture (such as the film Dead Poets' Society).